2006
DOI: 10.1063/1.2167352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of length and annealing conditions on magnetoimpedance of Co68Fe5Si12B15 amorphous ribbons

Abstract: The effect of conventional annealing and Joule annealing on magnetoimpedance (MI) of Co68Fe5Si12B15 ribbons was studied. The ribbons used for the MI measurements were 1 and 5 cm long. The as cast 5-cm-long ribbons exhibit a larger MI compared with the 1-cm-long ribbons, at all frequencies. The maximum MI of the as cast ribbons of 5 cm length is 17% at 600 kHz whereas for the 1-cm-long ribbons it is 3% at 500 kHz. Conventional annealing carried out at 200 and 300 °C for 1 h results in the decrease of the MI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Vazquez et al [11] reported that the GMI effect decreased in Fe-based nanocrystalline wires as the wire length decreased from 8 to 1 cm. A similar trend was also observed for the case of Co-based amorphous ribbons [12][13][14], Febased nanocrystalline ribbons [15,16] and CoSiB/Cu/CoSiB layered thin films [5]. However, Phan et al [17] reported that the decrease of length of a Co-based microwire from 4 to 1 mm resulted in a strong increase of the GMI effect.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Vazquez et al [11] reported that the GMI effect decreased in Fe-based nanocrystalline wires as the wire length decreased from 8 to 1 cm. A similar trend was also observed for the case of Co-based amorphous ribbons [12][13][14], Febased nanocrystalline ribbons [15,16] and CoSiB/Cu/CoSiB layered thin films [5]. However, Phan et al [17] reported that the decrease of length of a Co-based microwire from 4 to 1 mm resulted in a strong increase of the GMI effect.…”
Section: Introductionsupporting
confidence: 67%
“…For samples with L < L 0 , the decrease of GMI results mainly from the strong decrease of T due to the demagnetization effect. This explains why the GMI effect decreased with decreasing L in Co-based amorphous ribbons [12][13][14], Fe-based nanocrystalline ribbons [15,16] and CoSiB/Cu/CoSiB layered thin films [5]. Actually, the magnitude of L 0 depends on the type of domain structure [11,17,18], and it has been found that the critical length is shorter for Co-based wires than for Fe-based wires [18].…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations